2016
DOI: 10.1016/j.ajog.2016.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Assessing ureteral patency using 10% dextrose cystoscopy fluid: evaluation of urinary tract infection rates

Abstract: BACKGROUND: Intravenous indigo carmine has routinely been used to confirm ureteral patency after urogynecologic surgery. Recent discontinuation of the dye has altered clinical practice. In the absence of indigo carmine, we have used 10% dextrose in sterile water (D10) as cystoscopic fluid to evaluate ureteral patency. Glucosuria has been associated with urinary tract infection (UTI) in vivo and significantly enhanced bacterial growth in vitro. The concern is that the use of D10 would mimic a state of glucosuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 37 publications
0
16
1
Order By: Relevance
“…Despite these advantages in visualization, some practitioners have postulated that dextrose instillation may increase the risk of urinary tract infection (UTI) by providing an environment that promotes bacterial proliferation. A study by Siff et al [10] of women having dextrose compared with normal saline cystoscopy at the time of urogynecologic surgery demonstrated a 3.4-fold increased odds of UTI in the 10% dextrose group; however, the patients in this study had other risk factors for UTI including older age, postmenopausal status, and treatment condition (pelvic organ prolapse and incontinence). By contrast, a 2017 randomized control trial comparing surgeon satisfaction with 4 methods of evaluating ureteral patency found no difference in UTI symptoms between mannitol cystoscopy and other methods; they also found that mannitol bladder distention was the most satisfactory cystoscopy method [11].…”
Section: Study Objectivecontrasting
confidence: 70%
See 1 more Smart Citation
“…Despite these advantages in visualization, some practitioners have postulated that dextrose instillation may increase the risk of urinary tract infection (UTI) by providing an environment that promotes bacterial proliferation. A study by Siff et al [10] of women having dextrose compared with normal saline cystoscopy at the time of urogynecologic surgery demonstrated a 3.4-fold increased odds of UTI in the 10% dextrose group; however, the patients in this study had other risk factors for UTI including older age, postmenopausal status, and treatment condition (pelvic organ prolapse and incontinence). By contrast, a 2017 randomized control trial comparing surgeon satisfaction with 4 methods of evaluating ureteral patency found no difference in UTI symptoms between mannitol cystoscopy and other methods; they also found that mannitol bladder distention was the most satisfactory cystoscopy method [11].…”
Section: Study Objectivecontrasting
confidence: 70%
“…If a culture was done, a positive urine culture was defined by >100 000 microorganisms/mL with no more than 2 species present. This definition was based on the Centers for Disease Control and Prevention guidelines for UTI [12] and was also used in the previously mentioned Siff et al [10] study. No urinalyses were sent and thus could not be included in our definition of UTI.…”
Section: Methodsmentioning
confidence: 99%
“…A retrospective cohort study found that postoperative rates of UTI were higher in women underwent cystoscopy with 10% Dextrose at the time of intraoperative cystoscopy than using normal saline. 7 Flushing the bladder after finishing the cystoscopy could decrease the adherence of dextrose and uroepithelium. This may lead to a decrease in the postoperative rate of UTI.…”
Section: Dextrose Distension Mediamentioning
confidence: 99%
“…This may lead to a decrease in the postoperative rate of UTI. 7 Further study is needed to support this concept. Another disadvantage of using dextrose media is it can cause sticky equipment following use.…”
Section: Dextrose Distension Mediamentioning
confidence: 99%
“…They suggested cystoscopy with intravenous dye injection and placement of ureteral catheters before and after the surgery (9). Kwon CH et al ing ureteral patency (11). In patients with end stage renal disease requiring hemodialysis evaluation of ureteral patency during reconstruction surgery plays a fundamental role since to preserve residual renal function.…”
Section: Introductionmentioning
confidence: 99%